Association of schistosome infection with adiposity in Tanzania - Pham, Khanh; PrayGod, George; Faurholt-Jepsen, Daniel; Olsen, Mette F.; Kavishe, Bazil; Kitilya, Brenda; Corstjens, Paul L. A. M.; de Dood, Claudia J.; Friis, Henrik; Filteau, Suzanne; Downs, Jennifer A.; Peck, Robert N. (Frontiers in Public Health, 2023)
Background Observational studies in humans have reported a link between schistosome infection and lower adiposity, but this may be explained by socioeconomic and demographic factors, intensity of infection, or common co-infections such as HIV. Methods This was a cross-sectional study that investigated the relationship between schistosome infection and adiposity in a large, well-described cohort of Tanzanian adults living with and without HIV. Cross-sectional data were collected among adults living in Mwanza, Tanzania who were enrolled in the Chronic Infections, Co-morbidities and Diabetes in Africa (CICADA) cohort study. Schistosome circulating anodic antigen, secreted by both Schistosoma mansoni and haematobium which are endemic to Tanzania, was quantified from stored samples. Schistosome infection diagnosed by serum circulating anodic antigen levels. The primary outcome was fat mass measured by bioimpedance analysis. Secondary outcomes included fat-free mass, waist circumference, mid-upper arm circumference, and body mass index. Results The study enrolled 1,947 adults, of whom 1,923 (98.8%) had serum available for schistosome testing. Of these, 873 (45.4%) had a serum circulating anodic antigen ≥30 pg/mL, indicating schistosome infection. Compared to uninfected individuals, those with schistosome infections had −1.1 kg [95% CI −1.9 to −0.3] lower fat mass after adjusting for age, sex, physical activity, tobacco use, education level, and socioeconomic status. Infected participants also had lower waist circumference, mid-upper arm circumference, and body mass index. Fat-free mass was not different between the two groups. Neither being HIV-infected, nor receiving antiretroviral therapy, modified associations between schistosome infection and adiposity. These associations were also not affected by Schistosoma worm burden. Conclusions Schistosome infection was associated with lower fat mass and less central adiposity without a difference in muscle mass, irrespective of confounders, HIV status, or the intensity of schistosome infection. Future studies should adjust for socioeconomic and demographic factors that are associated with schistosome infection and adiposity. Identifying mechanistic pathways by which schistosome infection reduces adiposity while preserving muscle mass could yield new strategies for obesity control and cardiovascular disease prevention.